Bidirectional neuron-glioma interactions: effects of glioma cells on synaptic activity and its impact on tumor growth. (12th October 2019) - Tantillo, Elena; Vannini, Eleonora; Cerri, Chiara; Maria Mazzanti, Chiara; Costa, Mario; Caleo, Matteo
Abstract: Gliomas grow in a neuronal environment, but little is known on the functional changes in peritumoral neurons during tumor development. Moreover, investigations on the role of neural activity in glioma progression have yielded contradictory results. Here, we monitored longitudinal changes in network activity by recording visual evoked potentials (VEP) and local field potentials (LFP) after transplant of GL261 glioma cells in mouse visual cortex. We detected a progressive deterioration of VEP amplitudes in glioma-bearing mice, accompanied by an increase in slow network oscillations. At the cellular level, the analysis of microdissected peritumoral neurons showed alterations in both pre- and post-synaptic markers. To investigate whether glioma-driven alterations in synaptic function may impact on tumor growth, we manipulated levels of afferent cortical activity in glioma-bearing mice. Specifically, we tested blockade of synaptic activity via botulinum neurotoxin A (BoNT/A), visual deprivation (dark rearing, DR) and visual stimulation (VS). Replicating cells were quantified via immunostaining for BrdU and Ki67. We found that manipulation of cortical activity bidirectionally regulated glioma proliferation. Silencing of cortical synapses with BoNT/A and DR increased tumor proliferation while daily VS had the opposite effect. These findings demonstrate reduced responsiveness of peritumoral neurons which may in turn stimulate tumor cell proliferation, thus triggering a vicious loop that exacerbates glioma progression. Physiological stimulation of neural activity appears to restrain glioma proliferation so it could be implemented in the clinical setting as an adjuvant therapy.